Ecology of terrace wet rice-fish environment and role of periphyton - Saikia, Surjya Kumar; Das, Debangshu Narayan (Journal of Wetlands Ecology, 2011)
The waterlogged terrace wet rice-fields of Apatani Plateau located at an altitude of 1500msl in Arunachal Pradesh of the north eastern India are stocked with fish Common carp (Cyprinus carpio L) for several decades. The fishes are not fed with supplementary feeds because of the rich organic nature of the rice-fields. The study on water and soil of these fields revealed a strong co-relation to such organic nature. The wet rice-fish integrated fields exhibited the characters of shallow wet ecosystems. The water canals traversed through the rice fields were found inundated with water up to 50m showing the nature of Deep Water Rice fields (DWR) at least for one month. Significant (p<0.001) variations of water were observed for dissolved oxygen (DO) and carbon dioxide (CO2) to diurnal and seasonal changes. Alkalinity of the fields intends to play a role towards its productivity which is otherwise played by DO in other aquatic systems. Soil nitrogen reflected a gradual increasing trend of organic nature. Role of periphyton may not be ignored to the high phosphorus level of the soil at later flood phases in these fields. Key words: Rice-fish; aquatic ecosystem; organic practice; plankton; periphyton DOI: 10.3126/jowe.v4i0.2585 Journal of Wetlands Ecology, (2010) Vol. 4, pp 102-111